2022
DOI: 10.1155/2022/8479012
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Tribological Properties of Hybridized Palm Kernel Shell Ash and Nano Boron Nitride Reinforced Aluminium Matrix Composites

Abstract: The tribological properties of hybridized reinforced aluminium matrix composites were optimized using Taguchi and Grey Relational Analysis in conjunction with an L16 orthogonal array. The combination of palm kernel shell ash (PKSA) (0–5 wt. %) along with nano BN reinforcements was taken in interest. Loads and speeds (500, 750, 1000, and 1250 rpm) were employed as control parameters for the experiment. Using a Taber type abrasion machine, the wear samples were made, and the wear experiments were carried out. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Tests and delimitation theory have shown that the subsurface experiences deformations during the sliding wear process, with the largest plastic strain occurring under the contact area [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tests and delimitation theory have shown that the subsurface experiences deformations during the sliding wear process, with the largest plastic strain occurring under the contact area [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The base area of the still is 0.36 m 2 (0:6 m length × 0:6 m breadth). The taller side wall has a 2 International Journal of Photoenergy height of 0.5 m and the shorter side wall has 0.2 m. To increase the absorptive, black paint has been applied to the basin's interior surface [24][25][26]. The basin is protected with glass which allows the solar radiation to reach the basin plate and also acts as the condensing surface.…”
Section: Methodsmentioning
confidence: 99%
“…The specimens are placed into an ASE-UTN 10 controlled by computers UTM. until the failure occurs on the samples [23][24][25]. This happens at room temperature.…”
Section: Tensile Testmentioning
confidence: 99%